Understanding the Broader Impacts of COVID-19 on Women and Girls in the DRC through Integrated Outbreak Analytics to Reinforce Evidence for Rapid Operational Decision-Making. Issue 1 (1st March 2022) - Carter, Simone; Scott Moncrieff, Izzy; Akilimali, Pierre Z.; Kazadi, Dieudonné Mwamba; Grépin, Karen A.
Abstract: Whilst men and boys account for more COVID-19 cases and deaths, the secondary impacts of the outbreak on women and girls in the Democratic Republic of the Congo are cross-cutting and far-reaching. School closures put girls at increased risk of adolescent pregnancy, sexual violence and early marriage; more women working in the informal sector have lost jobs and been affected by closures of markets and borders; and frequent restrictions on sexual and reproductive healthcare have impacted access to services for women. Lessons learnt from previous health crises can help to highlight the extent of these issues. However, a lack of sex disaggregated data around COVID-19 morbidity and mortality in the DRC means that it is impossible to fully measure and understand the impact of the outbreak on women and girls or develop and implement appropriate interventions. This article presents a meta-synthesis of existing and ongoing analyses to highlight the broader impacts of COVID-19 on women and girls in the country.